PENGARUH PEMAPARAN MEDAN MAGNET 0,2 mT PADA MEDIA YANG MENGANDUNG LOGAM (Al, Pb, Cd, dan Cu) TERHADAP Bacillus sp DALAM MENGHASILKAN PROTEASE - Sumardi Sumardi; Rochmah Agustrina; Bambang Irawan; Shofia Rodia (Research Center for Biology-Indonesian Institute of Sciences, 2020)
This study aimed to determine the effect of 0.2 mT magnetic field exposure on metals (Al, Pb, Cd and Cu) containing media, to proteolytic index of Bacillus sp., protease activity and cell morphology of Bacillus sp. This study consisted of three stages. The first stage was a proteolytic test on solid media containing milk. The second stage was the production of protease enzymes in liquid media. The third stage was Scanning Electron Microscopy (SEM) analysis on a culture treatment known as protease enzyme activity. The results showed that the largest proteolytic index on CuCl2 metal ion content of magnetic 0.2 mT magnetic field for 10 minutes increased the value of the largest proteolytic index was 4.33. While in the ion solution containing CdCl2, Bacillus sp. culture did not grow. In the production of enzymes in the liquid medium, the highest enzyme activity (0.140 U/ ml) was produced on a medium containing AlCl3 and exposed to magnetic fields. The SEM analysis also proved that the supplementation of AlCl3 increased cell length by 2.38 and 2.78 times longer than control without magnetic field and for magnet field, respectivelly.